Cell Growth, Lipid Production and Productivity in Photosynthetic Micro-alga Chlorella vulgaris under Different Nitrogen Concentrations and Culture Media Replacement - Morowvat, Mohammad H.; Ghasemi, Younes (Recent Patents on Food, Nutrition & Agriculture, 2018)
Background: The photosynthetic unicellular microalgal strain, Chlorella vulgaris is considered as a robust biomass and lipid producer for human food and feed and also green energy production. The culture media composition plays a crucial role in biomass and lipid production and productivity. Methods: The photosynthetic green microalga C. vulgaris was studied in three distinct cultivation experiments each for 22 days, using BG11 and f/2 culture media to investigate the effects of different levels of nitrogen and culture media replacement on cell growth, lipid production and productivity. Results: In f/2 culture medium, the total lipid production reached was 0.246 g L-1 (41.55%) which was 147% higher than its counterpart in BG11 medium (0.298 g L-1). On the other hand, the highest biomass (1.492 g L-1) was attained in BG11-3 medium with 6.00 g nitrate L-1 and this was correlated with higher total chlorophyll content (15.189 mg L-1) and cell number (3.812 106 cell mL-1). A fatty acid profile, composed of saturated, monounsaturated and polyunsaturated fatty acids was detected and included stearic acid, oleic acid, α-linolenic acid and γ-linolenic acid which have nutritional or combustion importance. Conclusion: These data suggest that this C. vulgaris strain may be considered as a robust source for biomass, lipid and green energy production. The newly established patents have shed light on the future directions to achieve higher lipids and fatty acids with improved properties through different bioprocess and genetic engineering approaches.
Keywords: Cell growth